2021
DOI: 10.1016/j.msard.2021.103324
|View full text |Cite
|
Sign up to set email alerts
|

The MuSC-19 study: The Egyptian cohort

Abstract: Objective : This study aimed to report the severity of COVID-19 in a cohort of Egyptian patients with multiple sclerosis (MS) with particular attention on the impact of disease modifying drugs (DMDs). Methods and study population : We included 119 MS patients recruited from two centers, Ain-Shams university and Cairo university with confirmed or suspected COVID-19 during the period from May to September 2020 as a part of the MuSC-19 project. Univariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Thus, the risk of COVID-19 in our patients with MS was likely related to noncompliance to the preventive measures, as expected in younger patients. Furthermore, our findings were similar to reports published from Saudi Arabia and the region ( Alshamrani et al, 2021 , Zakaria et al, 2021 , Sahraian et al, 2020 , Sen et al, 2021 ). A recent meta-analysis reported a pooled prevalence of 4 % of COVID-19 in patients with MS, with 10 % hospitalization and pooled death rates of 4 % ( Moghadasi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the risk of COVID-19 in our patients with MS was likely related to noncompliance to the preventive measures, as expected in younger patients. Furthermore, our findings were similar to reports published from Saudi Arabia and the region ( Alshamrani et al, 2021 , Zakaria et al, 2021 , Sahraian et al, 2020 , Sen et al, 2021 ). A recent meta-analysis reported a pooled prevalence of 4 % of COVID-19 in patients with MS, with 10 % hospitalization and pooled death rates of 4 % ( Moghadasi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…24,33,34,36 Regarding disease-modifying drugs (DMDs) several good and reasonable studies showed no impact of their use in the susceptibility to SARS-Cov-2 infection. 24,26,32,38 Interestingly, older studies from 2020 showed the same preliminary results despite lack of confirmation of SARS-Cov-2 infection. 47…”
Section: Immunosuppressive Therapy and Sars-cov-2 Infectionmentioning
confidence: 82%
“…These studies were classified as "fair" or even "poor". 22,32,42 On the other hand, public health protection measures influenced people's behaviour, with different results for similar studies in similar cohorts. The importance of the public health measures in the context of COVID-19 was mentioned by Ramirez et al associating them with the lower number of COVID-19 cases in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also evaluate the performance of the score in other countries. Differences in hospitalizations rates among countries can indeed depend on quality and accessibility of Health Service but also on the national guidelines regarding the hospital admission of the patients ( Fragoso et al, 2021 Oct , Zakaria et al, 2021 Nov ). As first preliminary analysis or in the absence of studies presenting specific-region scores, for patients outside Italy, Turkey and South America, the score may be calculated on the basis of which of the three regions is the most similar to the country under study in terms of National Health Service and Covid-19 cases management.…”
Section: Discussionmentioning
confidence: 99%